A Probabilistic Model for Evaluation of the Dynamic Behavior of a Concrete Gravity Dam considering the Fluid-Structure Interaction - Majid Pasbani Khiavi; Adel Ferdousi; Abdolrahman Moallemi Khiavi (Advances in Civil Engineering)
Regarding the importance of the interaction effect in the dynamic behavior of a concrete dam and reservoir, the process of hydrodynamic wave propagation in the reservoir and its effects on the response of a concrete gravity dam are examined in this article by presenting a new probabilistic model. For this purpose, a program has been written in an APDL environment of Ansys software capable of dynamic analysis of a system and presenting probabilistic models. The Monte Carlo method with the LHS method has been applied for the probabilistic model, in which the essential parameters in the dam-reservoir interaction problem include excitation frequency, reservoir height, and reservoir length as input variables, and the effect of their changes on the hydrodynamic wave propagation process in the reservoir and the dynamic response of the dam are evaluated. For a better understanding of the dam-reservoir interaction concept and to show the capability of the presented model, two simple and isolated models of the concrete gravity dam and reservoir system have been considered. According to the results, the distribution trend of hydrodynamic pressure along the reservoir can be obviously recognized. Also, the results present the dependence of the responses and the propagation status on the excitation frequency and its relationship with the system frequency and the reservoir natural frequency.